The development of the Questionnaire of (Central) Auditory Processing: a screening tool of auditory processing - Tabone, Nadine; Grech, Helen; Bamiou, Doris-Eva (Frontiers in Audiology and Otology, 2024)
The aim of this study was to develop a screening questionnaire for auditory processing disorder (APD) targeted for the Maltese paediatric population.The questionnaire consisted of 25 close-ended questions in which parents rated their child's listening skills. The data was collected from 101 typically developing Maltese bilingual children and 30 children forming a clinical group, aged between 7;00 and 9;11 years.The tool was found to be highly reliable with an internal consistency of .92 and test-retest reliability of .94. Significant differences emerged between normal and clinical groups (p=<.001). Correlational analysis demonstrated a significant correlation between the Questionnaire of (Central) Auditory Processing (QCAP) and the speech-in-noise test, Duration Patterns Test and tests of dichotic listening.The QCAP is potentially an effective screening tool for highlighting listening difficulties in Maltese children at risk of having APD.